The Politics of Indonesia's Decentralization Law Based on Regional Competency - Prasetyo, Ngesti Dwi; Fadli, Moh.; Anshari SN, Tunggul; Ali Safa’at, Muchamad (Faculty of Law, Universitas Brawijaya, 2021)
Local governments have undergone various regulatory developments since Indonesia's independence 75 years ago. Various aspects underlying the development and changes in local government policies can be analyzed using several approaches, such as historical, philosophical, and sociological. This paper will discuss how the legal politics of the development of local government implementation, especially in terms of decentralization. Furthermore, the author will explain about the opportunities for implementing decentralization based on regional capacity to promote welfare of society. This research is normative juridical research using historical approach, conceptual approach, and legal approach. It can be said that the implementation and development of local government implementation is strongly influenced by various aspects other than the legal factor itself. Furthermore, there is still the possibility of implementing decentralization based on regional capacity as an effort to promote social welfare.